NATURE OF IMMUNE DISORDERS IN PATIENTS WITH ENT ABNORMALITIES AND METHODS OF THEIR CORRECTION - Popov, N.N.; Ognivenko, E.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Immune disorders in patients with ENT abnormalities both of systemic and local nature as well as disorders related to different parts of the immune system have been examined in our survey. Long term inflammatory processes in the mucous membrane of the respiratory tract result in suppression of local defense mechanisms and weakness of general immune reactivity of the body. The clinical course of the disease, its duration and number of complications depend on the nature and degree of immune disorders. Taking into consideration frequent immunodeficiency conditions occurring in patients with inflammation of the upper air passages, we have also reviewed the aspects of modern immunotherapy the medicines of immunostimulating and immunomodulating action being of the great interest.